Increasing effectiveness of the science-policy interface in the socioecological arena in Brazil. (December 2019) - Scarano, Fabio R.; Padgurschi, Maíra C.G.; Pires, Aliny P.F.; Castro, Paula F.D.; Farinaci, Juliana S.; Bustamante, Mercedes; Metzger, Jean P.; Ometto, Jean P.; Seixas, Cristiana S.; Joly, Carlos A.
Highlights: BPBES is the first national-level science-policy platform to emerge inspired by IPBES It navigates the implementation space by building boundary chains of organisations Differently from regular scientific panels, BPBES is designed to continually update reports Challenges include fatigue, stakeholder engagement, and fundraising BPBES experience can inspire other national level initiatives Abstract: A group of scientists created in 2015 the Brazilian Platform on Biodiversity and Ecosystem Services (BPBES), the first national-level initiative to emerge independently but inspired by the enterprise undertaken by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES). The main goal of BPBES is to develop assessment and special reports in co-production and dialogue with governmental and non-governmental stakeholders in Brazil, but independently from governmental perusal. This paper describes BPBES's principles, design, routine practices, outputs, achievements, challenges, near-future perspectives, and costs. After three and a half years of activities, BPBES emerges as a link that connects various organisations within a boundary chain at the science-policy interface. By navigating the socioecological arena, engaging with various actors, we argue that BPBES is an emerging important player in conservation and sustainable use of biodiversity and ecosystem services in Brazil. Differently from the regular scientific panel that produces assessment reports and special reports from time to time, we discuss the BPBES approach whereby such reports are due to be continuously updated by a system that combines consultation to and engagement of multiple actors, curators of specific themes, revision work, and communication to non-expert audiences. Challenges include how to avoid fatigue typical of extensive participatory processes, how to deal with the issue of representativeness of stakeholders selected, and long-term fundraising strategy. Finally, we discuss the potential relevance of other national level initiatives to facilitate on-the-ground implementation of practices and aspirations fostered by intergovernmental panels.